Intra/Sections : Towards Post-Anthropocentric Concepts of Multiplicity - Haase, Jenny,; Thiele, Kathrin, (Dispositiv der Menge ;, 2025)
The global socio-ecological crisis is making it increasingly clear that 'we' do not only act in interpersonal social and political relationships, but that non-human forms of life and relationships must also be taken into account in the critical analysis of our present. In light of that realization, this volume opens the question of the Menge (multitude, crowd) towards a post-anthropocentric perspective on multiplicity. Based on speculative readings of works by K. Barad, M. de la Cadena, and C. Vicuña, the essays illuminate how a human-and-more-than-human intra/sectional approach can help deconstruct the western hegemonic framework in contemporary cultural thinking from a transdisciplinary perspective.